Investigating the Factors Influencing Effective Teaching Dimensions in Iraqi Art Education - Shaalan Alkhafaji, Dhafer Habeeb; Mosavi, Faranak; Rashid Almamori, Khudhair Jasim; Karimi, Fariba (AI and Tech in Behavioral and Social Sciences, 2024)
This study examines the factors influencing the dimensions of effective teaching in Iraqi art education. This research is applied-developmental in nature and is a non-experimental (descriptive) study in terms of data collection method. The population of the study includes all art teachers in Iraq. The sample size was estimated to be 384 using Cochran's formula. Data analysis was performed using SPSS and Smart PLS statistical software. The findings indicated that the effectiveness of art teaching, the role of art in society, and educational infrastructure influence educational policy. Additionally, teaching style influenced the effectiveness of art teaching, educational policy was impactful in formulating an art course charter, and finally, factors related to the teacher and curriculum content were influential on the effectiveness of art teaching.